2008
DOI: 10.17305/bjbms.2008.2980
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Hormonal and Lipid Status in Women in Menopause

Abstract: It is widely accepted that menopause leads to changes in hormonal status, metabolism and lipid profile. The aim of this study was to analyze the influence of menopause on the concentrations of lipids, lipoproteins and, the influence of estradiol, progesterone, FSH, LH on lipid profile in menopausal women as well. The menopausal women had higher but non-significant (p>0,05) concentrations of total cholesterol, VLDL, LDL, and triglycerides than women with regular menstruation. The concentration of HDL was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 18 publications
3
22
1
3
Order By: Relevance
“…In this present study, fasting blood sugar were increased in postmenopause group compared to the premenopause group and it also shows that serum HDL cholesterol levels were on the lower side and minimum value being 21 mg/ dl in postmenopause group when compared to the premenopause group. Our finding is matched with previous studies 15,16 This said that the fasting blood sugar is increased whereas serum HDL cholesterol levels had lowered in postmenopause group compared to the premenopause group.…”
Section: Discussionsupporting
confidence: 92%
“…In this present study, fasting blood sugar were increased in postmenopause group compared to the premenopause group and it also shows that serum HDL cholesterol levels were on the lower side and minimum value being 21 mg/ dl in postmenopause group when compared to the premenopause group. Our finding is matched with previous studies 15,16 This said that the fasting blood sugar is increased whereas serum HDL cholesterol levels had lowered in postmenopause group compared to the premenopause group.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Mesalić et al (78) reported a favorable profile in postmenopausal women with higher estrogen levels, the latter correlating positively with HDL and negatively with VLDL and triglyceride concentrations.…”
Section: Lipid Profilementioning
confidence: 99%
“…Menopause is defined as cessation of menstruation for a period longer than one year, and begins with changes in ovarian function. 1 The median age for the final menstrual period is about 51 years, when the ovarian follicular reserve and indeed oestrogen production is significantly reduced. 2,3 A woman from her intrauterine life till the end experiences have a higher risk for coronary heart disease (CHD) than those with low AIP.…”
Section: Introductionmentioning
confidence: 99%